Citrus Diseases Exotic to Florida: Black Spot - Kuang-Ren Chung; Natalia A. Peres; Lavern W. Timmer (EDIS, 2005)
The authors' intent is to: 1) provide a basis for evaluating exotic pathogens that may pose potential risks to Florida citrus; and 2) to create a decision-making framework to prevent their introduction and spread. This paper will discuss citrus black spot. This document is Fact Sheet PP-213, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2005.